ANALISIS DAMPAK PENAMBANGAN EMAS TANPA IZIN (PETI) MUARO KIAWAI TERHADAP HASIL TANGKAPAN IKAN DI TPI SASAK, KABUPATEN PASAMAN BARAT - Frinsis Warmansyah; Lismomon Nata; Eri Barlian; Nurhasan Syah; Abdul Razak; Iswandi Umar (Universitas Fort De Kock, 2023)
In recent years, Unlicensed Gold Mining (PETI) has been rampant in Indonesia. Although the activity of searching for precious metals provides many benefits, it also has an impact on damage to the ecosystem and the environment. This provides its own dynamics by policy makers, entrepreneurs and regions as mining loci. Therefore, awareness and management as well as appropriate policies and laws are needed. This study aims to determine the relationship and impact arising from the Upstream Unlicensed Gold Mining (PETI) on fish catches at TPI Sasak which is the downstream part. This research was conducted in Muaro Kiawai, West Pasaman Regency in 2022. The research method was carried out using a qualitative approach with analytical techniques using Environmental Sustainable Analysis (ESA). The results showed that there was a relationship and the impact of PETI on water quality and the effect of weather on fish catches. In conclusion, it can be seen that PETI will affect the ecosystem and environment around mining